(untitled) (American Journal of Physical Education and Health Science, 2025)
This research initiative is dedicated to developing a comprehensive wellness program for female freshman students. The primary focus is to promote optimal health through education on proper nutrition and the encouragement of regular physical activity, aiming to improve overall well-being and reduce the risk of chronic health conditions. The program underscores the university’s commitment to fostering a vibrant physical fitness and wellness culture among students and staff. It aims to systematically review and assess existing programs and events that enhance engagement in physical activities and promote sportsmanship within the campus community. The research employs rigorous quantitative methodologies to create an effective wellness program, including detailed surveys and statistical analysis techniques. These methods are crucial in gathering reliable data to ensure that the wellness program closely aligns with female freshman students’ unique needs, preferences, and interests at the University of the Philippines Los Baños (UPLB). Ultimately, the initiative seeks to generate valuable insights into young women’s health and wellness concerns, thereby developing a tailored wellness program that addresses their specific health needs and supports their personal goals and aspirations throughout their college experience.